FAKTOR KONTEKSTUAL DAN INDIVIDUAL TERHADAP JUMLAH ANAK LAHIR HIDUP: SEBUAH ANALISIS MULTILEVEL - Sari Kistiana; Sri Lilestina Nasution; Margareth Maya P Naibaho (Research Centre for Population, Indonesian Institute of Sciences, 2020)
Since 1971, the total fertility rate in Indonesia consistently declined, but from 2002-2003 to 2012, the rate is stagnant at 2.6. Recently, Indonesia’s total fertility rate was increased slightly from 2.34 in 2016 to 2.40 children in 2017. This study analyzed individual and contextual factors that affect the number of children ever born based on the 2017 RPJMN KKBPK Survey. The survey collected data from 52,340 women aged 15-49 years old. The analytical approaches for this study are descriptive and inferential techniques using a two-level multilevel regression with a random intercept. All predictor variables at level 1 and level 2, namely individual factors (contraceptive use, marital status, age at first sexual intercourse, childhood mortality, health insurance coverage, contraceptive knowledge, age, work status, economic status and marital frequency) and contextual factor (area of residence) are found to have a significant effect on children ever born. The dominant factors influencing the number of children ever born are age at first sexual intercourse, age, marital frequency and childhood mortality.